2016
DOI: 10.3892/or.2016.4913
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of microRNA-203a expression in breast cancer

Abstract: Tumor heterogeneity and the poor outcome of breast cancer (BC) patients have led researchers to define new markers of this disease. In recent years, microRNA expression patterns have proven to be valuable disease indicators. The level of miR-203a, in particular, was shown to be altered in different types of cancer. The objective of the present study was to assess the relationship between miR-203a expression and clinicopathological features of BC in a Portuguese cohort. The expression levels of miR‑203a were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…The crosstalk between lncRNAs and miRNAs has been reported to control cancer progression [21]. miR-203a has been found to be a crucial regulator involved in various cancers, such as gastric cancer [22], nasopharyngeal carcinoma [23], breast cancer [24], lung cancer [25], live cancer [26], and CRC [27]. However, the potential involvement of miR-203a in the chemoresistance of CRC is not well known.…”
Section: Introductionmentioning
confidence: 99%
“…The crosstalk between lncRNAs and miRNAs has been reported to control cancer progression [21]. miR-203a has been found to be a crucial regulator involved in various cancers, such as gastric cancer [22], nasopharyngeal carcinoma [23], breast cancer [24], lung cancer [25], live cancer [26], and CRC [27]. However, the potential involvement of miR-203a in the chemoresistance of CRC is not well known.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, downregulated miR-203a-3p expression was detected in gastric cancer ( 35 ), prostate cancer ( 36 ), non-small-cell lung carcinoma ( 37 ) and esophageal cancer ( 38 ). However, only one study has identified the expression and potential functions of miR-203a-3p in BC; Gomes et al ( 21 ) reported that the expression of miR-203a-3p was markedly upregulated in 109 BC samples compared with matched normal breast samples and also identified that upregulated expression of miR-203a-3p was established in five clinic pathological characteristics groups: Tumor size ≤18.5 mm, HER2-negative, PR-positive, ER-positive and high Ki-67 index groups.…”
Section: Discussionmentioning
confidence: 99%
“…Since the sample size of the study by Gomes et al ( 21 ) was not large or varied enough, the current study combined data from three projects with a larger sample size to ensure the accuracy of the results. It was identified that the expression of precursor miR-203a was significantly elevated in 1,077 BC tissue samples compared with 104 adjacent breast tissue samples in TCGA project data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of such studies on BC samples, we decided to perform a pilot research on those 28 BC confirmed patients who had all of our inclusion criteria (between December 2013 and April 2014). Moreover, most studies measuring miR expression level have used formalin-fixed paraffin-embedded (FFPE)-paired normal and tumor tissue samples; whereas our study was performed on fresh frozen tumor samples ( 23 - 27 ), that their RNA yield was expected to be higher ( 28 ). Clearly, obtaining and preparing fresh frozen samples are much more difficult and time- consuming.…”
Section: Methodsmentioning
confidence: 99%